2002
DOI: 10.1103/physrevb.66.085322
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of open quantum billiards and classical trajectories

Abstract: We analyse the transport phenomena of 2D quantum billiards with convex boundary of different shape. The quantum mechanical analysis is performed by means of the poles of the S matrix while the classical analysis is based on the motion of a free particle inside the cavity along trajectories with a different number of bounces at the boundary. The value of the conductance depends on the manner the leads are attached to the cavity. The Fourier transform of the transmission amplitudes is compared with the length of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 46 publications
0
37
0
Order By: Relevance
“…The resonance wave function ͉⌽ R (x,y)͉ 2 displays a strong localization along the convex boundary, which is a characteristic feature of the WGM. 10 In the SIS, these trajectories almost exclusively correspond to one bounce at the convex boundary, while for the Bun1 billiard, there is also a small contribution of trajectories with two bounces. In the SIS the WGM accumulate Rϭ ͚⌫ WGM / ͚ i ⌫ i Ͼ98% of the total sum of widths ͚⌫ i of all states, while in the Bun1 billiard they accumulate a fraction Rϭ93% of the total sum.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…The resonance wave function ͉⌽ R (x,y)͉ 2 displays a strong localization along the convex boundary, which is a characteristic feature of the WGM. 10 In the SIS, these trajectories almost exclusively correspond to one bounce at the convex boundary, while for the Bun1 billiard, there is also a small contribution of trajectories with two bounces. In the SIS the WGM accumulate Rϭ ͚⌫ WGM / ͚ i ⌫ i Ͼ98% of the total sum of widths ͚⌫ i of all states, while in the Bun1 billiard they accumulate a fraction Rϭ93% of the total sum.…”
mentioning
confidence: 95%
“…As a consequence, the conductance of the quantum cavity significantly exceeds the prediction of RMT. 10 It is well established that shot noise ͑the zero-frequency current-current correlations caused by the discreteness of electric charge͒ provides valuable complementary information not contained in the conductance ͑for a review see Ref.11͒. It was found that correlations due to Fermi statistics suppress the shot-noise power P by a factor Fϭ P/ P 0 below the maximal value P 0 ϭ2eG 0 V of incoherent transport, with e the unit of charge, G 0 the series conductance of the two point contacts, and V the applied voltage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both time scales are well separated from one another. An example are the short-lived whispering gallery modes in a microwave cavity with convex boundary which coexist with many long-lived states, for details see [5][6][7]. The dynamical phase transitions are surely the most interesting feature of non-Hermitian quantum physics [1,8].…”
mentioning
confidence: 98%
“…Both time scales are well separated from one another. A theoretical example are the shortlived whispering gallery modes in a small microwave cavity with convex boundary which coexist with many long-lived states, for details see [20][21][22]. An experimental example are the isobaric analogue resonances in medium -mass nuclei.…”
Section: Resonance Trapping and Dynamical Phase Transitionsmentioning
confidence: 99%